DETERMINANT FACTORS THAT AFFECT E- LEARNING APPROACH IN TEACHING AND LEARNING AT HIGHER EDUCATION: A LITERATURE REVIEW - Halimatus Sakdiyah Hosayni; Nur Fatin Syawani Suhaimi; Abdullah Muhamed Yusoff; Roslizawati Che Aziz; Nik Alif Amri Nik Hashim; Anis Nazihah Ahmad Nordin (Jurnal Penyelidikan Sains Sosial, 2020)
Recently, the eLearning market has growth up successfully as a result from theemerging of eLearning as the new paradigm of modern education. eLearning act as a mediumconsisting of various types of computer and electronic media which is communication tool aswell as the Internet which provides training and certain subjects. By using eLearning, studentscan attend online classes anywhere, regardless of time and place. Generally, eLearning is moregeared towards self-training and is ideal for individuals who work full-time but desire to furthertheir studies. Thus, this study was developed and integrated the factors that lead to theeffectiveness of eLearning approach in Teaching and Learning (T&L) system. The outcomes ofthis research will be helpful in developing new learning approach hence it is expected that theresult of this study will reveal the effectiveness of eLearning based on few elements such as ICTskills, time management, resources and learning technique.